2023
DOI: 10.1021/acs.jpcc.3c01221
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Molybdenum Dioxide Ultrathin Nanowire Bundles for Highly Sensitive, Stable, and Reproducible Surface-Enhanced Raman Spectroscopy

Abstract: In surface-enhanced Raman spectroscopy (SERS) detection, it is important to improve the sensitivity, stability, and reproducibility of semiconductor surface-enhanced Raman scattering (SERS) substrates. Here, a simple chemical method was used to synthesize molybdenum dioxide ultrathin nanowire bundles. The ultrathin nanowire bundles of molybdenum dioxide demonstrate distinct and robust surface plasmon resonance (SPR) effects within the visible light range. As a low-cost SERS substrate, the plasmonic molybdenum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…As a commonly used transition metal oxide, molybdenum dioxide (MoO 2 ) holds many advantages such as high electrical conductivity, high melting point, and good chemical stability, which make it an attractive material for various applications including catalysis, sensors, supercapacitors, Li-ion batteries, cancer therapy and surface-enhanced Raman scattering (SERS). 17–21 For example, Lou and co-workers have developed a facile solvothermal process and subsequent thermal treatment strategy to obtain a unique triple-shelled MoO 2 /carbon composite, which exhibited high electrochemical performance and excellent cycling stability in lithium-ion batteries. Xi et al reported that metallic MoO 2 can be used as a SERS substrate to detect trace amounts of high-risk chemicals including bisphenol A (BPA), dichlorophenol (DCP), and pentachlorophenol (PCP).…”
Section: Introductionmentioning
confidence: 99%
“…As a commonly used transition metal oxide, molybdenum dioxide (MoO 2 ) holds many advantages such as high electrical conductivity, high melting point, and good chemical stability, which make it an attractive material for various applications including catalysis, sensors, supercapacitors, Li-ion batteries, cancer therapy and surface-enhanced Raman scattering (SERS). 17–21 For example, Lou and co-workers have developed a facile solvothermal process and subsequent thermal treatment strategy to obtain a unique triple-shelled MoO 2 /carbon composite, which exhibited high electrochemical performance and excellent cycling stability in lithium-ion batteries. Xi et al reported that metallic MoO 2 can be used as a SERS substrate to detect trace amounts of high-risk chemicals including bisphenol A (BPA), dichlorophenol (DCP), and pentachlorophenol (PCP).…”
Section: Introductionmentioning
confidence: 99%